STUDENTS’ VISUALIZATION IN READING AND THEIR COGNITIVE LEARNING STYLES - Addinna, Ainul; Ovilia, Ririn; Asfina, Risda (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2019)
Empirically visualizing the text being read into pictures, diagrams, or images evidently deepens students’ reading comprehension. Given the evidence of its significance, this study aims to figure out the effect of visualizing the text upon the students’ reading comprehension observed from their cognitive learning styles namely field dependent (FD) and field independent (FI). Due to its purpose, the experimental study, quasy-experimental research to be specific, was carried out. Fifty four fifth-semester students at Universitas Negeri Malang participated in this study. The findings were shockingly contradictory with the empirical evidence provided in previous studies. It is revealed that visualization strategy was proven to be significantly ineffective in enhancing students’ reading comprehension on account for some factors. However, the mean score of FI students in experimental group was slightly above FD students.